Seminar Nasional Pengabdian Masyarakat (SEMNASKAT 2022) PHBS – Cuci Tangan Pakai Sabun (CTPS) - Ahmad Haikal Kahfi; Barkah Musyarofah; Niang Pranadaniati; Usni Hasanudin (Jurnal Nusantara Berbakti, 2023)
The problem faced by the people of Puri Bukit Depok is that there is still a lack of knowledge about the procedures for clean and healthy living behavior, so that the extension education program is the solution. The implementation method of this clean and healthy lifestyle program is through counseling, discussion and field action. Counseling and discussion activities are only 30% of 100% of the program's activities, the rest are direct activities in the field, namely counseling and how to live clean and healthy behaviors carried out by the KKN 64 group and assisted by several representatives from local youth organizations so that this activity can run smoothly. held. The result of this program is increasing public knowledge about how to live a clean and healthy life.